PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN E-COMMERCE UNTUK MENUMBUHKAN JIWA ENTERPRENEUR PADA KOMUNITAS PENCINTA IKAN HIAS - Hamdani, Agus Umar; Suryadi, Lis; Indra, Indra; Triyono, Gandung (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2021)
Most of the residents in the RT run the Micro, Small and Medium Business Units (UMKM). Although some business actors have used information technology tools to support their business, they are only limited to posting products via Facebook, Twitter, Instagram and WhatsApp. Residents do not understand how to sell and market products using information technology tools. In addition, product sales turnover tends to decline during the Covid-19 pandemic and large-scale social restrictions (PSBB), due to the lack of buyers. E-Commerce is an information system technology device that can be an alternative solution in an electronic-based sales system. With the use of E-Commerce technology, business actors can market their products online anywhere and anytime. Based on the above conditions, we conducted training to build a business using Electronic Commerce (E-Commerce) technology for residents in the RT 03 RW 02 Pondok Jati Jurangmangu Barat environment in order to foster an entrepreneurial spirit based on information technology (Technopreneur). The end result of this community service activity is that residents of RT 03 RW 02 Pondok Jati Jurangmangu Barat gain knowledge and experience regarding the use of E-Commerce technology, and get assistance in building E-Commerce websites.